Cultural Sustainability through Digital Learning: Integrating Technology in Lulo Dance Education - A. Nongko, Pahenra; Salma, Sitti; Said, Hasmira; Usman, Usman; Rohmiati, Rohmiati (Journal of Leadership, Management and Policy in Education, 2025)
The rapid development of technology offers new possibilities for preserving and promoting local cultural wisdom in the modern education system. This research explores the integration of technology into the learning of Lulo, a traditional dance from Southeast Sulawesi, as a means to improve education and cultural preservation. The aim is to examine how digital devices such as virtual reality, mobile apps, and online platforms can effectively engage students in learning traditional cultural practices. This study used 67 respondents, data was collected by qualitative analysis through interviews, observations, and surveys involving educators and students in schools that incorporate technology in the teaching of Lulo dance. Thematic analysis is used to identify key patterns in the use of technology for cultural education and their impact on student engagement and cultural understanding. The results of the study were in the aspects of technology integration (63.18%), learning experience (65.17%), cultural preservation (58.21%), and quality of education (61.69%) were very effective. shows that technology significantly improves student engagement and learning outcomes. However, challenges such as the digital divide and the need to maintain cultural authenticity are also identified. The study concludes that integrating technology in cultural education presents an effective strategy for cultural preservation, with implications for education policy, curriculum development, and the creation of culturally sensitive digital learning tools.